The Impact of the SEMAGI Programme on Learning Concentration in Early Childhood - Yonastutik, Desi Dwi; Maulana T, Mochammad; Muarif, Syamsul; P, Eky Prasetya (Journal of Childhood Development, 2025)
SEMAGI is a breakfast habituation program given to early childhood as an effort to provide children with an understanding of the importance of breakfast in the morning to improve concentration in learning at school. The purpose of this study was to determine the impact of the SEMAGI program habituation on learning concentration in early childhood at SPS Kamboja 4 School, Sukowono District, Jember Regency. This study used a pre-experimental research approach with one group pretest-posttest design. Data analysis used in this study used t-test analysis to determine the impact of breakfast habituation on learning concentration in early childhood as seen from the significance of the difference in learning concentration before and after being given the SEMAGI program. The pre-test results showed that out of 25 samples, 16 (64.0%) respondents had poor learning concentration and 9 (36.0%) respondents had good learning concentration, while in the post-test, 7 children (28%) still had poor learning concentration, while 18 children (72%) had good concentration. The results of the t-test analysis showed a significant difference in learning concentration before and after the SEMAGI program with a t value of 2.736 and a p value of 0.012. These results show a significant number because the p value <significance level (α) = 5% (0.05). Based on these results, it can be said that the SEMAGI program has a positive impact on learning concentration in early childhood at SPS Kamboja 4 School, Sukowono District, Jember Regency. Based on the research that has been conducted, students are accustomed to having breakfast to support children in concentrating when receiving learning at school.